Geographic Community-based Mobility Model - Zhang, Wendong; Gui, Xiaolin; An, Jian; Jiang, Jinghua (Elektronika ir Elektrotechnika, 2012)
Mobility model plays a crucial role in performance evaluation of mobile wireless networks. However, the majority of existing mobility models either does not exhibit realistic movement characteristics or modeling methods are too complex. In this paper, inspired from the trend that users usually move between several popular areas in daily movement, a new mobility model based on Geographic Community (GCMM) is proposed. We concern with the topology construct of geographic environment and the destination selection scheme for user moving in GCMM. Simulation result shown that GCMM better depict the mobility patterns of human. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2815